Eltrombopag Improves Refractory Thrombocytopenia in a Patient with Systemic Lupus Erythematosus. (15th August 2018) - Shima, Natsuki; Sumida, Keiichi; Kawada, Masahiro; Sekine, Akinari; Yamanouchi, Masayuki; Hiramatsu, Rikako; Hayami, Noriko; Hasegawa, Eiko; Suwabe, Tatsuya; Hoshino, Junichi; Sawa, Naoki; Takaichi, Kenmei; et al.
Abstract : A 42-year-old woman with systemic lupus erythematosus (SLE) was admitted to our hospital for evaluation of severe thrombocytopenia. She was treated with steroids, intravenous cyclophosphamide, intravenous immunoglobulin, and plasma exchange, but her thrombocytopenia did not improve. Renal biopsy showed class IV-S(C) + V lupus nephritis, according to the classification of the International Society of Nephrology/Renal Pathology Society. The PA-IgG and serum thrombopoietin (TPO) levels were elevated. Her thrombocytopenia responded to off-label administration of eltrombopag, which was discontinued after 42 months. At 18 months after stopping eltrombopag, the platelet count was 19.3 × 10 4 / μ L. Eltrombopag may be a therapeutic option for SLE patients with severe thrombocytopenia refractory to conventional therapy.